Empowering Students Through Digital Literacy: A Case Study of Successful Integration in a Higher Education Curriculum - Quraishi, Tamanna; Helena ULUSI; Asma MUHID; Musawer HAKIMI; Mohammad Reshad OLUSI (RADINKA JAYA UTAMA PUBLISHER, 2024)
This study investigates the integration of digital literacy into higher education curricula, focusing on its impact at Online Women University. The introduction delineates the importance of digital literacy in preparing students for success in the digital era. The purpose of the study is to explore the implications of digital literacy integration, encompassing student perceptions, experiences, and technology usage patterns. Methodologically, a cross-sectional research design was employed, with data collected from 150 participants, including students and lecturers, using convenience sampling. Surveys were administered to capture insights into digital literacy, technology usage, and educational experiences. Both descriptive and inferential analyses, including frequencies, percentages, ANOVA, chi-square tests, and regression analysis, were conducted to discern relationships and patterns. Results indicate varying levels of digital literacy integration across faculties, with notable differences in technology usage and perceived empowerment through digital literacy. Notably, the mean score for post-test digital literacy skills increased significantly compared to pre-test scores. The study also reveals high confidence levels in using digital tools for academic purposes among students, influenced by factors such as experience and training. In conclusion, the findings underscore the importance of integrating digital literacy into higher education curricula. They highlight the need for ongoing support and training to enhance digital literacy skills among students and educators. Despite limitations such as convenience sampling, the study contributes valuable insights into the role of digital literacy in academia, emphasizing its significance in preparing students for the digital challenges of the future.